Efficacy of Probiotics as Adjunctive Therapy to Nonsurgical Treatment of Peri-Implant Mucositis: A Systematic Review and Meta-Analysis - Zhao, Rui; Hu, Huimin; Wang, Yan; Lai, Wenli; Jian, Fan (Frontiers in Pharmacology, 2021)
Background: Peri-implant mucositis (PiM) is an inflammation of the soft tissues surrounding the dental implant and is the precursor of the destructive inflammatory peri-implantitis. PiM is usually reversible, but difficult to eradicate. Mechanical debridement (MD) is the conventional procedure to treat PiM although not enough to reach a complete resolution. Recently, probiotics have been considered in the treatment of peri-implant disease. Therefore, the aim of this systematic review and meta-analysis was to investigate the efficacy of the probiotic therapy combined with MD compared with MD alone or MD + placebo in patients with PiM. Methods: A search using electronic databases (MEDLINE, Science Direct databases, and Cochrane Central Register of Controlled Trials) and a manual search were performed up to November 2019 by two reviewers independently of each other. Eligible randomized controlled trials (RCTs) comparing MD + probiotic vs. MD were included. The quality assessment for all the selected RCTs was conducted according to the Cochrane Handbook for Systematic Reviews of Interventions. Probing depth reduction was selected as the primary outcome. Weighted mean difference (WMD) and 95% confidence interval (CI) were calculated for continuous outcomes, and odds ratio (OR) and 95% CI were calculated for dichotomous outcomes, using random effect models. This review was registered on the PROSPERO database (CRD42020213625). Results: Five eligible publications were included in this systematic review and four in the meta-analysis. As regards the implant, the WMD in the probing depth reduction between the test and control group was −0.12 mm [95% CI (−0.38, 0.14), p = 0.38], meaning that the adjunctive probiotic therapy was not improving PiM compared with MD alone or MD + placebo. The meta-analysis also showed no statistically significant results in the secondary outcomes (reduction of full mouth plaque index and full mouth bleeding on probing, absence of bleeding on probing at implant level, and changes in microorganism load and species). Conclusion: The findings of this systematic review and meta-analysis suggested that the additional use of probiotics did not improve the efficacy of MD in PiM treatment regarding clinical and microbial outcomes, at least in a short-term.